ЖИНОИЙ ЖAЗОЛAР ИЖРОСИ УСТИДAН ПРОКУРОР НAЗОРAТИНИНГ РИВОЖЛAНИШ ТAРИХИ - Эргашев А.Б (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The scientific article analyzes the emergence of control over the execution of punishments, its development during periods and the stages in this development. Also reflected in the article is the development of the legal framework of the prosecutor's control over the execution of punishments in the Republic of Uzbekistan.